Exploring life skills, research adaptation, and team building among basic medical postgraduates - Zhang, Qiqi; Yuan, Xiaoqing; Liu, Ziyu; Liu, Jie; Ousmane, Diabate; Wang, Junpu (Frontiers in Medicine, 2025)
IntroductionUnder the background of “basic top-notch 2.0” plan, taking the graduate students of Xiangya School of Basic Medical Sciences, Central South University as an example, to explore their current situations in life, academics, scientific research, and team collaboration, thereby offering insights for enhancing the quality of basic medical graduate education in China, achieving the plan’s objectives, and shaping relevant policies.MethodsAn online anonymous questionnaire was sent to graduate students of basic medicine majors in different grades of Xiangya School of Basic Medical Sciences, Central South University. The questionnaire included 24 questions covering different aspects of graduate life, and the data of 350 valid questionnaires were analyzed. The study reveals diverse academic backgrounds among basic medical graduate students, with nearly half (50%) originating from different disciplines.ResultsOver 14% of students reported encountering learning difficulties, and many tended to seek help from peers rather than supervisors due to limited communication with their advisors. Approximately 80% of graduate students had flexible time management, yet only 26% received sufficient stipends to cover daily expenses, with an equal proportion facing inadequate research funding. Academic engagement was moderate (54.7%), though some students demonstrated low participation enthusiasm. Notably, nearly one-third (33.3%) had no prior research experience before enrollment. While overall satisfaction with supervisors’ academic and research guidance was high (96.29%), senior students exhibited a slight decline in satisfaction. A strong preference for the teamwork environment was reported (86.57%), though the satisfaction of the graduating students with the team working atmosphere was somewhat lower. Finally, 20.86% expressed dissatisfaction with their overall graduate school experience.Discussion and conclusionData analysis revealed pertinent issues, serving as a reference for educational institutions across all levels in formulating policies, such as enhancing graduate student adaptation and academic experience, guiding graduate students to adapt to their specialties, establishing effective communication channels, reasonably managing their own time, boosting funding, constructing academic platforms, facilitating early scientific research collaborations, enhancing guidance, and fostering team building, among others, in order to improve the training model and mechanism and cultivate outstanding medical innovative talents.